HUBUNGAN ANTARA KEKUATAN OTOT TUNGKAI DAN KESEIMBANGAN TERHADAP KECEPATAN TENDANGAN SABIT DIPERGURUAN DOMAS CIMANDE KOTA PEKANBARU - Ramjan Ramjan; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on observations in the field, the writer found problems in the domas cimande fighter in Pekanbaru City in carrying out sickle kicks during training and / or sparing. The research objective was to see the relationship between leg muscle strength and speed, balance, and sickle kick and leg muscle strength and the relationship between balance and sickle kick speed in Domas Cimande, Pekanbaru City. The population which is also the sample in this study is 12 athletes of the martial arts at Domas Cimande in Pekanbaru City. The results of this study, there is a strong relationship between leg muscle strength and the sickle speed at Domas Cimande, Pekanbaru, where the rtabel level at the significant level α (0.05) = 0.576 means rcount (1.10)> rtabel 0.576. There is a strong relationship between the balance and the sickle speed in Domas Cimande, Pekanbaru, where the rtabel level at the significant level α (0.05) = 0.576 means rcount (1.02)> rtabel 0.576. Compete the relationship between leg muscle strength (X1) and balance (X2) to the sickle speed (Y). The coefficient appears double together between leg muscle strength and balance with sickle kick speed. Furthermore, there is a relationship where r table at the significant level α (0.05) = 0.576 means Rhitung (0.946)> rtabel (0.576).Key Words: Relationship, Leg Muscle Strength, Balance, Sickle Kick Speed